Empirical Study of Asset Pricing Models on Mexico's Stock Market - Larsen Van Alstine, Shannen (2019)
The purpose of this study is to examine the Mexico Stock Market and to then asses the asset pricing models used. The study will focus on the capital asset pricing model and the Fama French three factor model. Furtherly, to examine the potential uses of different models and the understanding of systematic risk. The empirical study is done for the purpose of further knowledge of the Mexico Stock Market and the implications it holds for investors. Based on 24 stocks from the Mexico stock market from June 1st, 2013 to January 1st, 2019 tested the models through linear and cross sectional regression of the individual stocks and within four portfolios ranked by the market performance beta. The study found that the Fama French three factor model is able to explain the excess returns from stocks with far more minimal variation than the capital asset pricing model.